The Multilingual Brain: An Experimental Study - van Zwet, Joyce (Student Undergraduate Research E-journal!, 2019)
This study investigates the organization of the mental lexicon in the multilingual brain in order to determine whether there is interaction between the lexicons of a speaker’s different languages. We performed a cross-language semantic priming experiment with Dutch native speakers having varying levels of French. We analysed our data in view of three models: the independent model (Kolers, 1963), the revised hierarchical model (Kroll & Steward, 2002) and the BIA+ model (Dijkstra et al, 2002). Our results support the independent model in which there is suggested that there is no interaction between the mental lexicons of the speakers’ languages.